Sams teach yourself JavaScript and Ajax video learning - Safari eBooks ([Indianapolis, Ind.] : Sams Publishing, 2009)
"The Sams Teach Yourself JavaScript and Ajax Video Learning course is organized into 24 lessons, each designed to be completed in 10 minutes or less"--Resource description page.
Web Basic Refresher -- Web Scripting with Javascript -- Introducing Ajax -- Server-Side PHP Scripting -- Advanced Ajax Programming.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed Feb. 17, 2010).
Keywords: JavaScript (Computer program language); Ajax (Web site development technology); Web sites -- Design; Electronic books